Pengaruh Store Atmosphere, Service Excellent Dan Kelengkapan Produk Terhadap Kepuasan Konsumen (Studi Kasus Pada Kedai Aftertaste Coffee Batu) - Isamahendra, Yusril; Basalamah, Muhammad Ridwan; Mawardi, M Cholid (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This study examines the impact of Store Atmosphere, Service Excellence, and Product Completeness on Customer Satisfaction at Aftertaste Coffee Batu. These three variables were selected due to their significance in enhancing Customer Satisfaction within the relatively competitive F&B industry. Using a quantitative survey method via Google Forms, data was collected from 125 respondents who had visited Aftertaste. The research results indicate that multiple linear regression analysis shows that Store Atmosphere, Service Excellence, and Product Completeness simultaneously have a significant effect on customer satisfaction, with an F-value greater than the F-table value (58.54 > 2.68). Partially, the t-values for each variable are Store Atmosphere (5.625), Service Excellence (4.200), and Product Completeness (3.875), all of which are positively and significantly related, as they exceed the t-table value of 1.65754 (t-value > 1.65754), with Store Atmosphere being the dominant factor. Based on the findings, it is recommended that Aftertaste focus on improving store atmosphere (design & cleanliness), service (staff training), and product completeness to enhance customer satisfaction. Keywords: Store Atmosphere, Service Excellence, Product Completeness, Customer Satisfaction.